Pathways to farmers' entrepreneurship: the role of entrepreneurial mindset - Ihou, Atsu Frank Yayra; Mansingh, J. Paul (Frontiers in Sustainable Food Systems, 2025)
PurposeThis study explores farmers' entrepreneurial mindset, specifically its role in mediating the relationship between motivation, communication, risk factors, and entrepreneurial intentions.MethodologyThe study was conducted in Tamil Nadu, India, with 201 farmers from four districts. The study performed Structural Equation Modeling (SEM) using SmartPLS 4. To examine the relationships, confirmatory factor analysis and path analysis with bootstrapping were employed.FindingsThe findings reveal that economic motivation and risk orientation significantly enhance entrepreneurial intentions through mindset dimensions such as autonomy, proactiveness, and risk-taking. Proactiveness and risk-taking behaviors significantly influence farmers' entrepreneurial intentions in value-added activities like rice processing and oil extraction. Innovativeness, however, had no significant direct impact. Farm type (rice vs. groundnut farming) significantly moderates the relationship between risk-taking and farmers' entrepreneurial intentions.OriginalityThis research offers unique insights into the entrepreneurial mindset of farmers in a developing region, emphasizing the importance of mindset dimensions in driving entrepreneurial intention, particularly in value-added agricultural activities.ImplicationsThe study suggests policymakers should integrate financial incentives, risk management training, and communication programs to enhance farmers' entrepreneurial intentions. Financial support programs like subsidies and microloans can strengthen economic motivation, while entrepreneurship training can enhance opportunity recognition, risk assessment, and strategic decision-making.